Cyclin D1 and PRAME expression in distinguishing melanoma in situ from benign melanocytic proliferation of the nail unit - Young Jae Kim; Chang Jin Jung; Hyoungmin Na; Woo Jin Lee; Sung Eun Chang; Mi Woo Lee; Chan-Sik Park; Youngkyoung Lim; Chong Hyun Won (BMC, 2022)
Abstract Background Distinguishing benign lesion from early malignancy in melanocytic lesions of the nail unit still remains a diagnostic challenge, both clinically and histopathologically. While several immunohistochemistry (IHC) stainings have been suggested to help discriminate benign subungual melanocytic proliferation (SMP) and subungual melanoma in situ (MIS), the diagnostic utility of IHC staining for cyclin D1 and PRAME has not been thoroughly investigated in melanocytic lesions of nail unit. Methods This retrospective study included cases of benign SMP and subungual MIS confirmed by biopsy at Asan Medical Center from January 2016 to December 2020. Cases of melanocytic activation without proliferation and melanoma where dermal invasion was identified were excluded. Cyclin D1 and PRAME expression was assessed by counting proportion of melanocytes with nuclear positivity under 200x magnification. Results A total of 14 patients with benign SMP and 13 patients with subungual MIS were included in this study. 11 patients with benign SMP (71.4%) and 5 patients with subungual MIS (38.5%) showed > 60% nuclear immunostaining for cyclin D1, respectively. While 13 patients with benign SMP (92.9%) showed totally negative staining for PRAME, 10 patients with subungual MIS (76.9%) exhibited > 50% nuclear immunostaining for PRAME. Using the cutoff of 10%, PRAME exhibited good overall discrimination between benign SMP and subungual MIS (AUC = 0.849, 95% CI = 0.659-0.957). Conclusions This study suggests that PRAME IHC staining as a reliable discriminator in distinguishing subungual MIS from benign SMP.